2009
DOI: 10.4049/jimmunol.0803840
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Links NKG2D Signaling to a CrkL Pathway Involved in Natural Killer Cell Adhesion, Polarity, and Granule Secretion

Abstract: The NK cell-activating receptor NKG2D plays a critical role in the destruction of malignant cells, but many of the cell-signaling mechanisms governing NKG2D-mediated cellular cytotoxicity are unknown. We have identified an NKG2D-mediated signaling pathway that governs both conjugate formation and cytotoxic granule polarization. We demonstrate that an interaction between the regulatory subunit of PI3K, p85, and the adaptor protein CrkL is required for efficient NKG2D-mediated cellular cytotoxicity. We show decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…2B4-mediated signaling is dependent on Src-family kinases such as Fyn, which is recruited to the cytoplasmic tail of 2B4 via the adapter SAP (11). This results in the activation of PLCg and PKC, which can in turn activate Rap1, a known regulator of inside-out signaling (33,34). Fyn can additionally promote the phosphorylation of ADAP and SKAP-55 (35), which are also involved in inside-out signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2B4-mediated signaling is dependent on Src-family kinases such as Fyn, which is recruited to the cytoplasmic tail of 2B4 via the adapter SAP (11). This results in the activation of PLCg and PKC, which can in turn activate Rap1, a known regulator of inside-out signaling (33,34). Fyn can additionally promote the phosphorylation of ADAP and SKAP-55 (35), which are also involved in inside-out signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that NK cell-mediated cytotoxicity might be downregulated by G-CSF through the PI3K/Akt and ERK/MAPK signaling molecules, and the PI3K/Akt signaling then decreased expression of cytotoxicity-related molecules, TPI, while the ERK/MAPK signaling may be involved in regulation of other genes, such as cellular adhesion, polarity, development, cytokine production and granule secretion. 27,28 Recently, clinicians have begun to use new agents such as plerixafor (AMD3100) to optimize the mobilization of HSC before transplantation for treatment of hematologic diseases and inborn errors of metabolism. 23,36 Our results may provide additional important information regarding regulation of NK cell activity for developers of potential drugs for advanced stem cell mobilization in HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Articles have reported that PI3K links NKG2D-activated signaling pathway in NK cells with cellular adhesion, polarity, development, and cytokine and granule secretion, 27,28 implying that inhibition of the PI3K/Akt The relative values were normalized to the internal glyceraldehyde-3-phosphate dehydrogenase control and were calculated from at least three independent experiments. All results were expressed as mean±s.d.…”
Section: Discussionmentioning
confidence: 99%
“…As previously emphasized, the activating NK cell receptors have distinct cytoplasmic domains, and thus, are likely to act as platforms for different signaling com- [44] . CrkL was shown to facilitate NKG2D signaling downstream of PI3K activation and, in turn, activate Rap1.…”
Section: Contact and Adhesionmentioning
confidence: 99%